ANALISIS FAKTOR PERILAKU PENCEGAHAN COVID 19 PADA MAHASISWA SEKOLAH TINGGI ILMU KESEHATAN HANG TUAH PEKANBARU TAHUN 2020 - christine vita purba; Nurhapipa .; Yuyun Priwahyuni; Agus Alamsyah; Ikhtiaruddin . (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
COVID-19 is a respiratory disorder that causes illness ranging from mild to severe symptoms caused by the Corona Virus. Riau Province was one of the areas affected by COVID-19 in Indonesia with a total of 66 positive cases as of May 7, 2020. Students are one of the groups at risk of contracting COVID-19. For student group is very important to prevent groups of students in their 20s who look healthy but can be a source of transmission to families who do not prevent COVID-19. This study was aimed to analyzed the behavioral factors of prevention of COVID-19 in STIKes Hang Tuah Pekanbaru students in 2020. This type of research was quantitative observational with a cross sectional design. The population in this study were all students of STIKes Hang Tuah Pekanbaru with a sample size of 301 people. Data were collected used a questionnaire and analyzed by univariate and bivariate used the Chi-square test. The results showed that there was a relationship between knowledge, attitudes, responses to personal protective equipment, and family support with the prevention of COVID 19 while there was no relationship between role of health workers with the prevention of COVID 19 among STIKes Hang Tuah Pekanbaru students. It is hoped that students will increase their knowledge and prevention of COVID 19.